Artificial Intelligence (AI) and Small and Medium Enterprises (SMEs) Competitiveness: Evidence from Nepal’s Emerging Digital Economy - Nrip Bahadur Kunwar; Avishek Bhandari (Contemporary Research: An Interdisciplinary Academic Journal, 2026)
This investigation is about the relationship between adoption of AI and competitive performance of SMEs of Nepal in context of changing digital economy. Through a quantitative research methodology, empirical data was gathered from 425 SME proprietors and senior managers, who are located in different areas of Kathmandu Valley, Pokhara, Biratnagar, Dhangadhi and other regional centers across Nepal. The research framework looks at four key determinants: adoption of AI technology, workforce digital competencies, organizational innovation capacity and data-driven decision-making processes and the collective impact on competitive performance measures such as operational productivity, market penetration capability and financial outcome. Multiple regression analysis indicates that AI adoption (β = 2.324, p< 0.01) and digital workforce skills (β = 1.872, p< 0.01) have a significant and positive impact on SME competitive positioning, whereas innovation capacity (β = 1.546, p< 0.01) and utilization of analytical data (β = 1.215, p< 0.01) also have a positive and relatively less significant impact on SME competitive positioning. Findings reveal the AI enabled enterprises have proved not only to be superior in operational efficiency, but are also superior in market responsiveness; infrastructural impediments and skills deficiencies in the workforce remain as major hindrances. This investigation makes a constructive contribution to academic discussion on technology competitiveness in the developing economic context that can provide precious insights to policy makers, financial institutions and entrepreneur players that strive to ensure an inclusive economic development through AI integration.